Estudo do processo de cristalização de sacarose a partir de soluções provenientes de cana-de-açúcar por resfriamento controlado - Merheb, Graciela de Amaral (2009)
Today, Brazil is the major producer and exporter of sugar in the world. In the last harvest 2008/2009, 31.5 millions tons were produced, of which 60% were exported providing a 40% of international market share. However, sugar is a product that has commercial difficulties, due to the hard restrictions, such as rates, subsidizes and technical barriers like the use of sulfur (input) in laundering. Because of this, the development of a technology for the production of sugar with superior quality, less cost and without sulfur for the laundering would be of great interest for the productive sector. The present work aims to study the process of crystallization of sucrose from sugar solutions of syrup and sugar cane by controlled cooling. A laboratory plant with production capacity of 1 kg of sugar per batch, installed in the laboratory of industrial development of the Sugarcane Technology Center (CTC) in Piracicaba was used for the present work. The results regarding the reduction of impurities initially present in sugar crystals through crystallization by controlled cooling were: 95% in color, 85% in starch and 80% in dextran. For the syrup classified as VVHP, reductions obtained in crystals through crystallization by controlled cooling were: 96% of the final color of the sugar (from 10,100 IU to 361 IU), 98% in the amount of ash conductivity, 84% in the amount of starch and 52% in the amount of dextran. Obtained the results led to the construction of a pilot plant by scaling the process that will be implemented in an industrial unit.